Phasing out of darkness: from sterile neutrino dark matter to neutrino masses via time-dependent mixing - Florian Goertz; Maya Hager; Giorgio Laverda; Javier Rubio (Journal of High Energy Physics)
Abstract Sterile neutrinos are a compelling candidate for generating neutrino masses and for elucidating the nature of dark matter. Astrophysical X-ray constraints on sterile neutrino dark matter decays, however, largely exclude the active-sterile mixing required to produce simultaneously the correct left-handed neutrino spectrum and keV-scale right-handed neutrino dark matter within a type-I seesaw framework. In this study, we demonstrate how these X-ray constraints can be circumvented through a time-dependent approach, thereby reviving a broad range of active-sterile mixing scenarios. Our minimal model incorporates two right-handed neutrinos, which form a two-component dark matter candidate, and an auxiliary scalar field that experiences a very late and still ongoing phase transition, leading to the spontaneous breaking of a global U(1) N symmetry. Prior to this phase transition, only the right-handed neutrinos are massive, while the left-handed neutrinos remain massless because of the scalar field’s vanishing expectation value. As the phase transition develops, the growing expectation value of the scalar field increases the active-sterile mixing, thereby opening dark matter decay channels and inducing neutrino masses. The time dependence allows the scenario to be consistent with X-ray constraints as well as current measurements of left-handed neutrino masses. The anticipated level of active-sterile mixing today is within the detection capabilities of the forthcoming TRISTAN (KATRIN) tritium-beta decay project. Additionally, cosmological surveys such as DESI or EUCLID and supernova neutrino observations can test the prediction of massless left-handed neutrinos prior to the phase transition.